Juridical analysis of legal certainty regarding the role of the Batam Business Entity and the Land Office in the land certificate transfer system in Batam City - Lilis Suriyani; H.M. Soerya Respationo; Erniyanti Erniyanti (Goodwood Publishing, 2025)
Purpose: This study aims to analyze the regulations, implementation, obstacles, and solutions related to legal certainty in the transfer of land certificate ownership in Batam City, where dual authority exists between the Batam Business Agency (BP Batam) and the Land Office. The research seeks to provide a comprehensive understanding of how institutional overlaps affect legal certainty for the public and business actors in a nationally strategic economic area. Methods: The study uses normative and empirical juridical approaches through statutory and sociological methods, collecting data from regulatory documents and interviews with BP Batam officials, land staff, and legal practitioners, analyzed under positive law, legal system, and legal certainty theories. Results: The findings reveal regulatory disharmony and institutional overlap between BP Batam and the Land Office that hinder legal certainty. Unintegrated administrative procedures, differences in information systems, and limited public awareness create delays and confusion in the transfer process. Conclusion: Legal certainty in Batam’s land administration requires regulatory harmonization, integrated service mechanisms, and the digital integration of land administration systems. Strengthening public legal awareness is also essential for ensuring equitable and effective land services. Limitation: This study is limited to Batam City as a case study and may not fully represent broader land administration issues in other regions of Indonesia. Contribution: The research contributes to academic discourse and policy recommendations on resolving institutional dualism in land administration. It provides insights into harmonizing regulations and integrating digital systems to ensure legal certainty and improve public trust in land services.